Totok Wajah untuk Relaksasi Ibu Nifas di Puskesmas Rangkasbitung, Lebak Banten - Rita Ariesta; Diah Yuli Anggraeni; Nanda Afrilianti; Eva Wati; Melia Arsya Subekti; Miftahul Zanah (Akademi Kebidanan La Tansa Mashiro, 2022)
Anxiety, postpartum is a period when the reproductive organs return to their pre-pregnancy state within six weeks after giving birth. One of the psychological disorders experienced by postpartum mothers is anxiety. This anxiety is usually caused by tension in life that can cause anxiety, namely individual traumatic events, both developmental and situational crises, such as catastrophic events. solutions to reduce anxiety. The purpose of the study was to determine the relationship between full-bloodedness and the decrease in anxiety levels in postpartum mothers at PKM Rangkasbitung in 2021. The research method was cross sectoral with a total population of 53. And the number of samples was 35. The sampling technique used a questionnaire. The results of the univariate analysis found that the results felt better. good (97.14%) and those who do not feel good (2.85%). The use of full-blooded face can be an alternative to reduce anxiety, especially for postpartum mothers to be free from anxiety and fear.